MINERALOGICAL COMPOSITION OF SUSPENDED PARTICLES PM10 IN THE PTOLEMAIS-KOZANI AREA, MACEDONIA, GREECE - Nikolaidou, P.; Triantafyllou, A.; Kantiranis, N.; Filippidis, A. (Bulletin of the Geological Society of Greece, 2016)
PM10 suspended particles were collected from the Kardia lignite mine (July 2009), the the campus of Technological Education Institution of Western Macedonia (December 2010) and the Kozani city centre (August 2005). The mineralogical composition and the amorphous materials content of the samples was determined by X-Ray Powder Diffraction method. All samples contain amorphous materials (43-66wt.%), calcite (13-37 wt.%), micas + clays (4-9 wt.%) and quartz (2-8 wt.%), while in three samples feldspars (2-11 wt.%) were detected. Anhydrite, which is a constituent of the fly ash and the bottom ash, was detected (6 wt.%) only in one sample from the area of Kardia mine. Gypsum was detected, in the Kardia mine (2 and 3 wt.%), in the Kozani city centre (8 wt.%) and in the University campus (13 and 14 wt.%). Gypsum is a constituent of the mined lignite, the stack-gas ash and the Saharan dust. That explains the higher concentrations of gypsum in the University campus on 1st and 2nd of December 2010, where the influence of Saharan dust on the atmospheric particulate matter levels in Western Macedonia was reported.